Progresifitas Pemikiran Hadis Muhammad al-Gazali - Arif Nuh Safri (Institut Ilmu Al-Qur'an (IIQ) An-Nur Yogyakarta Komplek PP An Nur Ngrukem PO BOX 135 Bantul 55702 Yogyakarta Tlp/Fax (0274) 6469012. http://jurnalannur.ac.id/, 2017)
Hadith as the second source of law in Islam, always will continue to get the spotlight or study that develops according to the times. Although the hadith is seen as the second source of law, the position of hadith is still very central in shaping the religious understanding of a particular person or group. It can even surpass the portion of the Qur’an as the main and principal source. This sides of the Hadith are regarded as explanations or details of the Qur’an. With such a very central position, then the study of hadith also experienced the development. For example, the development of Muhammad al-Ghazali. In this case, he tries to progressive in understanding the hadith, so what he does is not uncommon to get censured, and sharp criticism. This progressiveness he did with the aim of shaping the understanding of traditions that more adjust the times, or the demands of the international world. So that the teachings of Islam are considered highly relevant to the development of the times. Through this article, the author tries to explain how the pregresivitas thought of Muhammad al-Ghazali. The thought of alGhazali is based on personal anxiety and an awareness of the history and reality that is afflicting Muslims and Islamic countries that are always under the control and control of Western nations. How the thoughts and solutions offered by al-Ghazali in understanding hadith is necessary to be studied, so that the understanding of hadith in contemporary times is more significant and relevant to modern social conditions.